INOVASI MODEL SOSIALISASI PERAN SERTA MASYARAKAT DALAM PEMILU - Putra, Arry Dharmawan Trisatya (JWP (Jurnal Wacana Politik), 2016)
Political socialization was conducted by Electoral Committee as an attempt to foster public participation in the election of integrity. However, some factors are impeding public participation which needs to be overcome by the electoral committee. Therefore, innovative model of political socialization is needed to improve the quality of future election in Indonesia. Qualitative method is employed in this study to investigate the role of current political socialization and to find out an innovative way which should be undertaken by electoral committee to foster public participation in the election.Â